Resolvin D1 shows osseous-protection via RANK reduction on monocytes during orthodontic tooth movement - Klein, Yehuda; Levin-Talmor, Offir; Berkstein, Jaime Garber; Wald, Sharon; Meirow, Yaron; Maimon, Avi; Leibovich, Avi; Barenholz, Yechezkel; Polak, David; Chaushu, Stella (Frontiers in Immunology, 2022)
The study aimed to investigate the role of RvD1 in acute and prolonged sterile inflammation and bone remodeling. A mouse model of sterile inflammation that involves bone resorption was used to examine endogenous RvD1 kinetics during inflammation. Application of exogenous RvD1 significantly inhibited bone remodeling via osteoclast reduction, alongside an anti-inflammatory secretome shift, increased macrophages recruitment and reduction of T-cytotoxic cells. In vitro and in vivo, RvD1 led to significant reduction in RANK expression which reduce osteoclastogenesis in a dose-dependent manner. Taken together, the data shows a dual role for RvD1, as a potent immunoresolvent agent alongside an osteoresolvent role, showing a potential therapeutic agent in bone resorption associated inflammatory conditions.